2020
DOI: 10.3390/sym12111784
|View full text |Cite
|
Sign up to set email alerts
|

Spin and Polarization in High-Energy Hadron-Hadron and Lepton-Hadron Scattering

Abstract: The role of spin degrees of freedom in high-energy hadron-hadron and lepton-hadron scattering is reviewed with emphasis on the dominant role of soft, diffractive, non-perturbative effects. Explicit models based on analyticity and Regge-pole theory, including the pomeron trajectory (gluon exchange in the t channel) are discussed. We argue that there is a single, universal pomeron in Nature, manifest as relatively “soft” or “hard”, depending on the kinematics considered. Both the pomeron and the non-leading (sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Recent advances in spin physics have led to a proposal of using storage rings for the search of axion-like particles, which are one of the candidates for explaining the dark matter in the Universe. The details of spin degrees role, its studies and perspectivesstudies of these can be found in [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in spin physics have led to a proposal of using storage rings for the search of axion-like particles, which are one of the candidates for explaining the dark matter in the Universe. The details of spin degrees role, its studies and perspectivesstudies of these can be found in [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The Reference [3] reviews the role of spin in high energy hadron-hadron and leptonhadron interactions. It concerns mainly the nonperturbative sector of QCD, the roles of pomeron, odderon, unitarity, analyticity for spin observables and dependence of differential cross-section on the Mandelstam variables s and t with emphasis on Regge trajectories.…”
Section: Contributionsmentioning
confidence: 99%